2022
DOI: 10.1039/d1bm01142a
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of bryostatin-1 by targeted exosomes enhances remyelination and neuroprotection effects in the cuprizone-induced demyelinating animal model of multiple sclerosis

Abstract: Demyelinating disease is a critical neurological disease, and there is still a lack of effective treatment methods. In the past two decades, stem cells have emerged as a novel therapeutic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…Upon CPZ withdrawal, myelination can be repaired gradually. 41,42 Therefore, CPZ mice have been widely used in the study of demyelination and remyelination in MS. 20 A CPZ mouse model was constructed by feeding a mouse with rodent chow containing 0.2% CPZ for 6 weeks to induce complete demyelination. Then, the mouse was fed with a normal diet and checked for the demyelination of the corpus callosum (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon CPZ withdrawal, myelination can be repaired gradually. 41,42 Therefore, CPZ mice have been widely used in the study of demyelination and remyelination in MS. 20 A CPZ mouse model was constructed by feeding a mouse with rodent chow containing 0.2% CPZ for 6 weeks to induce complete demyelination. Then, the mouse was fed with a normal diet and checked for the demyelination of the corpus callosum (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have proved that BDNF can promote the proliferation of OPCs. 17–20 In this study, the effect of engineered exosome-mediated BDNF on OPCs in the corpus callosum of CPZ model mice was studied by PDGFRα immunofluorescence staining. The results indicated that RVG/BDNF-Exo significantly promoted the increase in the number of PDGFRα + OPCs in the corpus callosum region, which plays a positive role in remyelination (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomes derived from neural stem cells were targeted using a lentivirus-armed PDGFR-alpha ligand capable of anchoring the membrane [ 116 ]. Exosomes modified in this manner appeared to be capable of targeting oligodendrocyte progenitor cells in the neural lesion area.…”
Section: Therapeutic Applications Of the Msc-secretome For Autoimmune...mentioning
confidence: 99%
“…This novel exosome-based delivery method significantly enhanced the myelin sheath’s ability to protect integrity and promote remyelination. Additionally, it inhibited astrogliosis and axon damage as well as pro-inflammatory microglia [ 116 ].…”
Section: Therapeutic Applications Of the Msc-secretome For Autoimmune...mentioning
confidence: 99%